Anthracycline-induced cardiomyopathy, an essential diagnostic and therapeutic problem in oncological practice - Bręborowicz, Elżbieta; Bręborowicz, Piotr; Litwiniuk, Maria; Tomczak, Piotr (Contemporary Oncology/Współczesna Onkologia, 2007)
For many years, anthracyclines have been used in chemotherapy. Nowadays, cytostatic therapy prolongs survival of patients, but in some it produces a cardiotoxic effect, which leads to iatrogenic myocardial injury and cardiomyopathy with symptoms of heart failure. In chemotherapy departments, the oncologist has become responsible for cardiotoxicity risk stratification in patients undergoing/planned for anthracycline therapy and early recognition of cardiac complications. Monitoring of left ventricular function is now an essential part of oncological procedures using cardiotoxic drugs. ACE inhibitors, AT1 receptor blockers, betablockers, diuretics and digoxin are drugs of choice in heart failure therapy